1992
DOI: 10.1126/science.1376003
|View full text |Cite
|
Sign up to set email alerts
|

Association of a 59-kilodalton immunophilin with the glucocorticoid receptor complex

Abstract: Immunophilins, a family of proteins that exhibit rotamase (peptidyl-prolyl cis-trans isomerase) activity in vitro, are expressed in many organisms and most tissues. Although some immunophilins can mediate the immunosuppressive actions of FK506, rapamycin, and cyclosporin A, the physiological role of the unligated proteins is not known. A 59-kilodalton member of the FK506- and rapamycin-binding class was found to associate in the absence of these drugs with two heat shock proteins (hsp90 and hsp70) and the gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(145 citation statements)
references
References 34 publications
5
137
1
2
Order By: Relevance
“…There are some larger, multidomain FKBPs and also cyclophilins found as constituents in high molecular mass steroid receptor complexes [31,32]. The FKBP52 (also known as HSP56, p59, FKBP59 or HBI) (reviewed in [33]) contains three domains which are homologous to the FKBP12 [34].…”
Section: Discussionmentioning
confidence: 99%
“…There are some larger, multidomain FKBPs and also cyclophilins found as constituents in high molecular mass steroid receptor complexes [31,32]. The FKBP52 (also known as HSP56, p59, FKBP59 or HBI) (reviewed in [33]) contains three domains which are homologous to the FKBP12 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, substances that dissociate these proteins may facilitate nuclear translocation of GR and augment GC action. Recently, a GRassociated heat shock protein, hsp 56, has been shown to be identical to an immunophilin, FK506-binding protein (Tai et al, 1992;Yem et al, 1992). The association between immunophilin and GR suggests that FK506 may influence steroid receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, GR associates with several heat shock proteins (Pratt, 1993;Smith and Toft, 1993). Recent studies showed that the GR complex also contains members of the immunophilin class of proteins (Tai et al, 1992). Furthermore, Yem et al (Yem et al, 1992) reported that FK506-binding protein (FK-BP) is associated with the GR complex.…”
mentioning
confidence: 99%
“…Readings in the shaded area constitute background+noise levels. Note that the Jurkat cell clones do not express the human GR measured by the chip, but instead high levels of stably-transfected rat GR not detected by the chip Oncogene Effects of dex treatment in lymphocytic leukemia P Obexer et al Interestingly, while the GR itself is induced by dex, three genes of the`repressed' list ( Table 2) encode proteins that have been found associated with the GR: hsp70 (Tai et al, 1992), the`immunophilin-like' protein phosphatase 5 (Silverstein et al, 1999) and a predominantly nuclear protein known under the names of glucocorticoid receptor-interacting protein (Zeiner and Gehring, 1995), receptor-associating protein of 46 kDa (RAP46; Zeiner et al, 1997) and hsp70-associated protein 46 (Hap46; Zeiner et al, 1999). RAP46 has been shown to inhibit GC-induced apoptosis (Kullmann et al, 1998).…”
Section: Effects On the Gr And Associated Proteinsmentioning
confidence: 99%
“…GC act by binding to the glucocorticoid receptor (GR), a protein that, in the absence of ligand, remains cytoplasmic by binding to a large, dynamic multiprotein complex containing heat shock protein molecules ± hsp90 or hsp90 plus hsp70 ± and an immunophilin component (Tai et al, 1992). The immunophilin moiety binds to hsp90 via its tetratricopeptide repeat domain and may be represented by any one of several proteins, such as FKBP51, FKBP52, CyP-40 or even protein phosphatase 5 (PP5) (Owens-Grillo et al, 1995;Silverstein et al, 1997Silverstein et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%